MicroRNAs in microglia: deciphering their role in neurodegenerative diseases - Jadhav, Shweta Pradip (Frontiers in Cellular Neuroscience, 2024)
This review presents a comprehensive analysis of the role of microRNAs in microglia and their implications in the pathogenesis of neurodegenerative diseases. Microglia, as the resident immune cells of the central nervous system (CNS), are pivotal in maintaining neural homeostasis and responding to pathological changes. Recent studies have highlighted the significance of miRNAs, small non-coding RNA molecules, in regulating microglial functions. In neurodegenerative diseases, such as Alzheimer's Disease (AD), Parkinson's Disease (PD), Amyotrophic Lateral Sclerosis (ALS), and Multiple Sclerosis (MS), dysregulated miRNA expression in microglia contributes to disease progression through various mechanisms such regulation of gene expression, as modulation of cytokine response and phagocytosis.This review synthesizes current knowledge on how miRNAs influence microglial activation, cytokine production, and phagocytic activity. Specific miRNAs, such as miR-155, are explored for their roles in modulating microglial responses in the context of neuroinflammation and neurodegeneration. The study also discusses the impact of miRNA dysregulation on the transition of microglia from a neuroprotective to a neurotoxic phenotype, a critical aspect in the progression of neurodegenerative diseases.